2020
DOI: 10.1111/hsc.13034
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Life Satisfaction and Quality of Life among People Living with HIV/AIDS in Kermanshah‐West of Iran

Abstract: AIDS has become a pandemic that has infected millions of people worldwide (Palwe, Dargar, & Tawri, 2018). According to the World Health Organization (WHO), there were about 37.9 million patients with HIV/AIDS worldwide in 2018 (WHO, 2018). Despite the considerable time and money invested to the treatment of AIDS, experts have not achieved a significant result to definitive treatment. Therefore, in the past two decades, World Health Organization and other partner organisations have emphasised the importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…One plausible explanation is the WHO's continued effort in improving HIV programs in low‐to‐middle income countries that have a disproportionately high prevalence of HIV [ 19 ]. While the WHOQOL‐HIV is known to be sensitive to CD4 count and disease stage, it has been shown to adequately address HIV‐specific health concerns [ 20 , 21 , 22 , 23 , 24 ]. Another HIV‐specific instrument, the MOS‐HIV, was predominantly being used in low‐income countries (38.1%).…”
Section: Resultsmentioning
confidence: 99%
“…One plausible explanation is the WHO's continued effort in improving HIV programs in low‐to‐middle income countries that have a disproportionately high prevalence of HIV [ 19 ]. While the WHOQOL‐HIV is known to be sensitive to CD4 count and disease stage, it has been shown to adequately address HIV‐specific health concerns [ 20 , 21 , 22 , 23 , 24 ]. Another HIV‐specific instrument, the MOS‐HIV, was predominantly being used in low‐income countries (38.1%).…”
Section: Resultsmentioning
confidence: 99%
“…However, the increasing number of people living with HIV/AIDS should be a warning sign for the public sector, which already cover the costs of HIV/AIDS treatments in Iran. To the best of our knowledge, there is little research investigating willingness to pay for HIV/AIDS-related services [23][24][25][26]. This study examined people willing to pay for a hypothetical HIV/AIDS insurance in Tehran and its related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Marriage or companionship is an essential source of social support. Social support is an essential buffer to stressful life events; it positively impacts an individual’s physical and mental well-being, performance, creativity and competence and brings resilience when confronting stressful situations [ 36 38 ]. For example, an Ethiopian systematic review showed that PLHIV with good social support were four times more likely to report higher HRQoL when compared to those without (AOR = 4.01, 95% CI 3.07–5.23) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%